1970
DOI: 10.3329/ptcb.v18i1.3264
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Regeneration and Flower Induction on Solanum nigrum L. from Pachamalai hills of Eastern Ghats

Abstract: Explants of Solanum nigrum L., collected from Pachamalai hills callused successfully on MS basal medium supplemented with IAA and BAP. The highest frequency of green compact callus and multiple shoots were obtained on MS containing 2.0 mg/l IAA and 0.5 mg/l BAP. The callus when cultured on MS basal medium fortified with different concentrations of BAP (3.0 -8.0 mg/l) and IAA (0.5 mg/l) showed multiple shoot formation. The highest frequency of multiple shoots was obtained on MS containing 6.0 mg/l BAP and 0.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Leaf explants showed high percentage of callus formation than nodal stem and shoot apex respectively (Figure 1 d-f). Similar successful induction of callus from S. nigrum L. on MS basal medium supplemented with IAA and BAP were also observed [11] . Ray et al (2011) observed the highest callusing on medium MS + 2.0 mg/l BAP and 0.5 mg/l NAA during in vitro cultivation and regeneration of S. melongena [12] .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Leaf explants showed high percentage of callus formation than nodal stem and shoot apex respectively (Figure 1 d-f). Similar successful induction of callus from S. nigrum L. on MS basal medium supplemented with IAA and BAP were also observed [11] . Ray et al (2011) observed the highest callusing on medium MS + 2.0 mg/l BAP and 0.5 mg/l NAA during in vitro cultivation and regeneration of S. melongena [12] .…”
Section: Resultssupporting
confidence: 74%
“…Similarly, Taghipour et al (2015) observed in case of eggplant that after three weeks some differentiated shoots were rooted and some others were needed to be subcultured on fresh rooting medium for additional root development [17] . The best rooting was obtained on MS medium containing 0.5 mg/l IBA in S. Nigrum culture [11] . In in vitro study of S. melongena, MS medium with 3.0 mg/l IBA gave the best result for root induction for average number and mean length of roots [18] .…”
Section: Resultsmentioning
confidence: 99%
“…In medicinal plant species like Gentiana lutea, (Petrova et al, 2011) 1 mg L -1 IBA was found effective for rooting. The best rooting was obtained on MS medium containing 0.5 mg/l IBA in Solanum nigrum (Kolar et al, 2008). On 3 mg L -1 IBA, rooting was obtained in Chlorophytum borivilianum (Bathoju and Giri, 2012).…”
Section: Discussionmentioning
confidence: 97%